2013
DOI: 10.1093/humrep/des452
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sperm head proteins involved in zona pellucida binding

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 56 publications
6
50
0
1
Order By: Relevance
“…It has been reported recently that they might play a role in human fertility (Kwon et al 2013 ). Consistent with this proposal, VDAC2 was found to be one of the putative sperm head membrane proteins that bind ZP (Petit et al 2013 ).…”
Section: Voltage-dependent Anion Channels (Vdacs)supporting
confidence: 74%
“…It has been reported recently that they might play a role in human fertility (Kwon et al 2013 ). Consistent with this proposal, VDAC2 was found to be one of the putative sperm head membrane proteins that bind ZP (Petit et al 2013 ).…”
Section: Voltage-dependent Anion Channels (Vdacs)supporting
confidence: 74%
“…Several methods of analysis have been developed to increase the identification of the low-abundance proteins on subcellular parts of the spermatozoa such as the head and flagellum (Cao et al 2006, Amaral et al 2013, Baker et al 2013, acrosomal matrix, , detergent-resistant membrane (Sleight et al 2005), phosphorylated proteins (Platt et al 2009), and proteins involved in capacitation (Ficarro et al 2003) and motility (Zhao et al 2007, Martinez-Heredia et al 2008, Chan et al 2009) and of sperm-egg interactions (Stein et al 2006, Petit et al 2013. In spite of the lack of a dynamic range of mass spectrometers to identify the low-represented proteomes, these 'shotgun' mass spectrometer approaches provide the opportunity to identify additional proteins involved in new or unexpected metabolic pathways for mature sperm (Amaral et al 2013).…”
Section: R31mentioning
confidence: 99%
“…Most of them have been developed using specific sperm antibodies (competitor or inhibitor) to prevent the binding of a candidate protein to the ZP or oocyte membrane. More global approaches have also been developed such as phage display technology (Naz 2005, Samoylova et al 2012, and the ZP affinity properties of sperm proteins have been analysed using different global and selective proteomic approaches (Stein et al 2006, Brewis & Gadella 2010, Belleannee et al 2011a, Petit et al 2013. Many protein candidates have been proposed following these in vitro studies, and more than 50 proteins have already been reported to be involved in sperm-egg interactions (Supplementary Table 1).…”
Section: Epididymal Surroundings and Sperm Proteins Involved In Egg-bmentioning
confidence: 99%
“…In addition, ZP2 and ZP3 can directly interact with voltagedependent anion channel 2 (VDAC2) (Petit et al, 2013). Because ion transport-based osmoregulation is the major function of the fish gill (Evans et al, 2005), we hypothesized that the expression of ZPs might be related to the ion transport of rare minnow gills, and this hypothesis constitutes the basis of our next investigation.…”
Section: Discussionmentioning
confidence: 98%